Metagenomic insights into the profile of antibiotic resistomes in a large drinking water reservoir - Dang, Chenyuan; Yu Xia; Zheng, Maosheng; Tang Liu; Liu, Wen; Qian Chen; Ni, Jinren (Environment International, 2020)
Reservoirs play a vital role in the control and management of surface water resources. However, the long water residence time in the reservoir potentially increases the storage and accumulation of antibiotic resistant genes (ARGs). The full profiles and potential health risks of antibiotic resistomes in reservoirs are largely unknown. In this study, we investigated the antibiotic resistomes of water and sediment during different seasons in the Danjiangkou Reservoir, which is one of the largest reservoirs in China, using a metagenomic sequencing approach. A total of 436 ARG subtypes belonging to 20 ARG types were detected from 24 water and 18 sediment samples, with an average abundance of 0.138 copies/cell. The overall ARG abundance in the sediment was higher than that in the water, and bacitracin and vancomycin resistance genes were the predominant ARG types in the water and sediment, respectively. The overall ARG abundance in the dry season was higher than that in the wet season, and a significant difference in ARG subtype compositions was observed in water, but not in the sediment, between the different seasons. The potential horizontal gene transfer frequency in the water was higher than that in the sediment, and the ARGs in water mainly came from the sediment upstream of the reservoir. The metagenomic assembly identified 14 contigs as ARG-carrying pathogens including Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa, and 3 of 14 carried virulence factors. Overall, the potential public health risks posed by resistomes in the water of the Danjiangkou Reservoir were higher in the dry season than in the wet season. Based on these results, strategies including sediment control and pathogen monitoring are suggested for water safety management in drinking water reservoirs.
Keywords: Antibiotic resistome; ARG host tracking; Drinking water source; Metagenomic sequencing; The Danjiangkou Reservoir